Sustainability and antifragility - Joost Platje (Economic and Environmental Studies (E&ES), 2015)
This paper treats about the problem of nitrogen oxides formation in the process of natural gas combustion. The analysis of the influence of selected combustion parameters on the concentration of NO, N2O and NO2 in the combustion products was done. From many factors determining NOx formation two was selected, ie temperature and residence time at the highest temperature zone, considering them to be particularly important. Detailed analysis of the absolute rate of NOx for various combustion temperatures was done with the use of commercial software CHEMKIN-PRO. Moreover, the paths of formation of above- mentioned compounds were determined. The main goal of the research is to analyze the impact of selected parameters of combustion process, such as temperature, on formation of thermal nitrogen oxides, with special emphasis on the chemistry of the process. The use of numerical methods to predict the products of combustion process, especially NOx, is of great importance in terms of ecological and economical aspects
Keywords: Q01; 330; sustainable development; sustainability; fragility; antifragility; subtractive epistemology